Gastrointestinal endoscopy in a low budget context: delegating EGD to non-physician clinicians in Malawi can be feasible and safe - Wilhelm, T. J.; Mothes, H.; Chiwewe, D.; Mwatibu, B.; Kähler, G. (Endoscopy, 2012)
Gastrointestinal endoscopy is rarely performed in low-income countries in sub-Saharan Africa. One reason is the lack of available medical doctors and specialists in these countries. At Zomba Central Hospital in Malawi, clinical officers (non-physician clinicians with 4 years of formal training) were trained in upper gastrointestinal endoscopy. Prospectively recorded details of 1732 consecutive esophagogastroduodenoscopies (EGDs) performed between September 2001 and August 2010 were analyzed to evaluate whether upper gastrointestinal endoscopy can be performed safely and accurately by clinical officers. A total of 1059 (61.1 %) EGDs were performed by clinical officers alone and 673 (38.9 %) were carried out with a medical doctor present who performed or assisted in the procedure. Failure and complication rates were similar in both groups (P = 0.105). Endoscopic diagnoses for frequent indications were generally evenly distributed across the two groups. The main difference was a higher proportion of normal findings and a lower proportion of esophagitis in the group with a doctor present, although this was significant only in patients who had presented with epigastric/abdominal pain (P < 0.001). In conclusion, delegating upper gastrointestinal endoscopy to clinical officers can be feasible and safe in a setting with a shortage of medical doctors when adequate training and supervision are provided.